Putative Multifunctional Signature of Lung Metastases in Dedifferentiated Chondrosarcoma. (16th February 2012) - Malchenko, Sergey; Seftor, Elisabeth A.; Nikolsky, Yuri; Hasegawa, Susan L.; Kuo, Sean; Stevens, Jeff W.; Poyarkov, Stas; Nikolskaya, Tatiana; Kucaba, Tamara; Wang, Min; Abdulkawy, Hakim; Casavant, Thomas; et al.
Abstract : Chondrosarcomas are among the most malignant skeletal tumors. Dedifferentiated chondrosarcoma is a highly aggressive subtype of chondrosarcoma, with lung metastases developing within a few months of diagnosis in 90% of patients. In this paper we performed comparative analyses of the transcriptomes of five individual metastatic lung lesions that were surgically resected from a patient with dedifferentiated chondrosarcoma. We document for the first time a high heterogeneity of gene expression profiles among the individual lung metastases. Moreover, we reveal a signature of "multifunctional" genes that are expressed in all metastatic lung lesions. Also, for the first time, we document the occurrence of massive macrophage infiltration in dedifferentiated chondrosarcoma lung metastases.